2005
DOI: 10.1007/s11176-005-0345-4
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of 5-Substituted 2-(3-Chloropropanoylamino)benzophenone syn- and anti-Oximes with Sodium Hydroxide

Abstract: Treatment of syn-oximes of 5-substituted 2-(3-chloropropanoylamino)benzophenones with equimolar amount of sodium hydroxide results in formation of syn-oximes of 5-substituted 2-propenoylaminobenzophenones. The corresponding anti isomers under the same conditions give a mixture of anti-oximes of 5-substituted 2-(propenoylamino)benzophenones and 18-membered 11,22-disubstituted 7,8,18,19-tetrahydrodibenzo[d,m][1,10,2,6,11,15]dioxatetraazacyclooctadecine-6,17(5H,16H)-diones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Both amide groups have E con®gurations, which are apparently determined by intramolecular NÐHÁ Á ÁO hydrogen bonds (Table 1). It is noteworthy that the formation of an intramolecular hydrogen bond between a H atom of the amide group and the oxime O atom in a sterically unfavoured seven-membered ring has also been found in the previously described molecular structure of 5-bromo-2-propenoylaminobenzophenone synoxime (Andronati et al, 2005). The angle between the planes formed by the two fused benzene rings is 79.0 (3) .…”
Section: Figurementioning
confidence: 59%
See 1 more Smart Citation
“…Both amide groups have E con®gurations, which are apparently determined by intramolecular NÐHÁ Á ÁO hydrogen bonds (Table 1). It is noteworthy that the formation of an intramolecular hydrogen bond between a H atom of the amide group and the oxime O atom in a sterically unfavoured seven-membered ring has also been found in the previously described molecular structure of 5-bromo-2-propenoylaminobenzophenone synoxime (Andronati et al, 2005). The angle between the planes formed by the two fused benzene rings is 79.0 (3) .…”
Section: Figurementioning
confidence: 59%
“…Azamacrocyclic compounds are interesting macrocyclic objects with regard to their spatial structures, their selfassembly, chemical and coordination properties, and their biological activity (Hiraoka, 1978;Gokel & Korzeniowski, 1982;Gokel, 1991;Cooper, 1992;Bradshaw et al, 1993;Lehn, 1995;Bradshaw & Izatt, 1997;Kulikov et al, 2005). Recently, we have reported on the synthesis, crystal structure (Dvorkin et al, 1985;Andronati et al, 2005) and chemical properties (Kulikov et al, 2003), in particular, complexation with lanthanides (Pavlovsky et al, 2004;Rusakova et al, 2005), of the 16-and 18-membered dibenzodioxatetraaza macrocycles shown in the scheme. We present here the investigation, by experimental and theoretical methods, of the structural features of the macrocycle of the title solvate, (I), which are relevant to its complexation capabilities.…”
Section: Commentmentioning
confidence: 99%